PENGARUH PENGGUNAAN METODE PEMBELAJARAN DAN PENILAIAN AUTENTIK TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Dahlan, Jafar (Jurnal Evaluasi Pendidikan, 2017)
This study was conducted at SMPN 5 and SMPN 8 Kota Tidore Kepulauan. The research method used is experimental method, while the study is done by using factorial 2x2 design. Samples were selected by using simple random sampling technique. The samples of this research are 84 students of 8th grade of the second semester of the 2015/2016 academic year. Data collection was done by measuring the ability of a mathematical representation of students. The hypothesis was tested by using analysis of variance (ANOVA). The results showed that there are positive implications between the methods of learning and authentic assessment to the students’ ability in mathematical representation.